COLORIMETRIC ASSAY OF ASPIRIN USING MODIFIED METHOD - Abdulkadir, Maadh Qusay; Al-Mudhafar, May Mohammed Jawad; Mohammed, Amera Abbas; Alzahawie, Suha K (Al-Nahrain Journal of Science, 2009)
In this research, we did this qualitative and quantitative study in order to improve the assay of aspirin colorimetrically using visible spectrophotometer. This method depends on aqueous hydrolysis of aspirin and then treating it with the ferric chloride acidic solution to give violet colored complex with salicylic acid, as a result of aspirin hydrolysis, which has a maximum absorption at 530nm. This procedure was applied to determine the purity of aspirin powder and tablet. The results were approximately comparative so that the linearity was observed in the high value of both correlation coefficient (R = 0.998) and Determination Coefficient or Linearity (R2 = 0.996) while the molar absorpitivity was 1.3´103 mole-1.L.cm-1. This improvement cancelled the acid or base aided hydrolysis which is widely used during aspirin assay. This method could be also applied to salicylic acid.